A hierarchical method for soil erosion assessment and spatial risk modelling: a case study of Kiambu district in Kenya. - Okoth, Peter F. (Wageningen University & Research, 2003)
Though a lot has been done and achieved in erosion research and control in Kenya, most of the erosion research methods have in the past put emphasis more on quantifying soil loss or measuring soil erosion, rather than pinpointing to areas that are likely to suffer soil erosion. In most cases the erosion processes have been assumed to occur in a uniform manner at all levels of the landscape hierarchy, and hence the results of one level observation can be factored to cover other levels for which data was not collected. This has resulted in many people extrapolating site-specific point data to cover wider geographic regions, assuming uniformity of the erosion process over the region. Another interesting aspect of soil erosion is that though most attention is normally put on the negative effects of soil erosion, soil erosion has also some beneficial effects. For example, the deposition of eroded soil material to lower areas has sometimes improved the quality of the soil receiving the sediment, thereby improving agricultural productivity of the depositional areas. There have however been suggestions that the problem of soil erosion has been exaggerated and not proven to actually diminish crop yields against the background of improved crop productivity improvement techniques. All theses schisms makes it necessary to engage in soil erosion research, either to disprove the sceptics or to provide other means of assessing and viewing the problem of soil erosion.